Ecological momentary assessments of night‐time drinking among California adolescents: bases for informing night‐time preventive interventions. (5th July 2021) - Lipperman‐Kreda, Sharon; Mair, Christina; Gruenewald, Paul J.
Abstract: Background and Aim: To inform the development of effective night‐time preventive interventions, our goal was to assess adolescents' residence (i.e. being at) and transitions across contexts during evening hours and risks for drinking and drinking‐related problems in relation to contexts and to these transitions. Design: Ecological momentary assessment and survey methods. Setting: Twelve mid‐sized cities (50 000–500 000 population) in California, USA from December 2014 to September 2015. Analytical sample: A total of 153 adolescents (mean age = 16.4, 46.2% female). Measurement: Initial conditions (e.g. past‐year heavy drinking, gender, best friend's approval of drinking); adolescents' residence (i.e. being at) and transitions between (a) their own homes, (b) others' homes and (c) public spaces (e.g. restaurants, parks, concert venues) at early, middle and late evening hours; drinking in these contexts at early, middle and late evening hours; and drinking‐related problems across evening hours. Findings: Risks for drinking were 23.5 times greater in others' homes ( P  < 0.01) and somewhat less in public spaces [odds ratio (OR) = 6.01, P  < 0.01], compared with own home. Risks for problems in any evening time were elevated in relation to being in others' homes (OR = 2.37, P  < 0.05) and public spaces (OR = 2.71, P  < 0.01) versus at own home. Drinking in others' homes was related to 5.9 times increase in odds of transitioning back to own home (OR = 5.93, P  < 0.05), 11.9 times increase in odds of remaining in others' homes (OR = 11.86, P  < 0.01) or 7.3 times increase in odds of transitioning from others' homes to public spaces (OR = 7.3, P  < 0.05). Initial conditions were associated with being in states, drinking and problems during evening hours and transitions across states. Conclusions: In California, adolescents who are older, female, Hispanic or have greater spending money may be more likely to be outside their own home during evening hours than adolescents who do not match those criteria. In turn, being outside one's home during evening hours appears to be related to greater risks for drinking and drinking‐related problems. Finally, transitions between contexts increased differential risks for drinking such that, for example, drinking in others' homes was highly related to transitioning to public spaces and less to returning to own home.